2023
DOI: 10.1111/jfb.15368
|View full text |Cite
|
Sign up to set email alerts
|

The ecological relevance of critical thermal maxima methodology for fishes

Abstract: Critical thermal maxima methodology (CTM) has been used to infer acute upper thermal tolerance in fishes since the 1950s, yet its ecological relevance remains debated.In this study, the authors synthesize evidence to identify methodological concerns and common misconceptions that have limited the interpretation of critical thermal maximum (CT max ; value for an individual fish during one trial) in ecological and evolutionary studies of fishes. They identified limitations of, and opportunities for, using CT max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 122 publications
0
37
0
Order By: Relevance
“…A species' preferred temperature often coincides with their optimal growth and metabolism (Macnaughton et al, 2021;Schulte et al, 2011), and these physiological parameters can often be found to correspond with increased activities and behaviours, such as feeding, reproduction, or avoidance responses (Crawshaw, 1977;Killen et al, 2013). Temperatures around a species' preferred temperature generally provide the greatest opportunity for energetically expensive activities (e.g., growth and reproduction), while temperatures towards the upper and lower ends of a species' thermal range tend to reduce or prevent them (Crawshaw, 1977(Crawshaw, , 1984Desforges et al, 2023). Research assessing the CT max of fishes has shown an activation of a behavioural response at temperatures leading up to CT max , which has been described as the agitation temperature (McDonnell & Chapman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A species' preferred temperature often coincides with their optimal growth and metabolism (Macnaughton et al, 2021;Schulte et al, 2011), and these physiological parameters can often be found to correspond with increased activities and behaviours, such as feeding, reproduction, or avoidance responses (Crawshaw, 1977;Killen et al, 2013). Temperatures around a species' preferred temperature generally provide the greatest opportunity for energetically expensive activities (e.g., growth and reproduction), while temperatures towards the upper and lower ends of a species' thermal range tend to reduce or prevent them (Crawshaw, 1977(Crawshaw, , 1984Desforges et al, 2023). Research assessing the CT max of fishes has shown an activation of a behavioural response at temperatures leading up to CT max , which has been described as the agitation temperature (McDonnell & Chapman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Critical thermal maxima (CTMax) or minima (CTMin) criteria are commonly used to understand potential thermal limits of fish species (Becker and Genoway 1979; Lutterschmidt and Hutchison 1997; Rajaguru 2002; Desforges et al 2023). Critical thermal limits are measured by a constantly increasing (CTMax) or decreasing (CTMin) temperature from an initial acclimation temperature until loss of equilibrium (LOE) in the fish is reached, such that locomotive movements are disorganized, and the fish loses the ability to escape from the conditions (Beitinger et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, acute changes to the thermal environment are expected to have detrimental consequences for wild ectotherms, including increases in mortality, elevated stress levels and altered immune functions (Roth et al, 2010; Genin et al, 2020; Jørgensen et al, 2022). Although some aquatic animals are regularly exposed to rapid temperature changes, for instance, while crossing the thermocline during vertical migrations or due to diurnal temperature fluctuations in shallow waters or intertidal zones (Bates & Morley, 2020; Desforges et al, 2023), exposure of shallow aquatic species to rapid thermal changes will likely be intensified due to increases in average surface water temperatures (IPCC, 2022). Thus, estimating the susceptibility of ectotherms to acute warming events is crucial to understand the risk posed by global climate change to wild populations.…”
Section: Introductionmentioning
confidence: 99%